Associations of sport participation with subjective well-being: a study consisting of a sample of Chinese school-attending students - Liu, Tianzhuo; Li, Dong; Yang, Hongying; Chi, Xinli; Yan, Jin (Frontiers in Public Health, 2023)
Abstract: Past studies have illustrated that the impact of sports participation on school-attending students' well-being plays a significant role in the life course of adolescence, which is a golden period for developing sound psychological qualities. However, the relationship between sports participation and subjective well-being is not clear, particularly in Chinese primary and middle schools. Purpose: Therefore, the current study was aimed to explore the relationship between sports participation and subjective well-being in elementary and middle schools in China. Method: All involved children and adolescents were asked to conduct a self-report of their sociodemographic factors (e.g., sex, grade, age), independence, and outcomes. The survey involved a two-stage sampling design (district school). China’s education system is a 6-3-3 system, including six years of primary school, three years of junior middle school, and three years of senior high school. Besides, in order to examine the relationship between participation in sports and subjective well-being, a self-report questionnaire was used. Logistic regression with 95% confidence interval and odds ratios (ORs), was conducted to investigate the relationship between sports participation and subjective well-being. Results: A total of 67,281 participants in total provided complete data for the final analysis of the current study. The percentage of boys and girls was 51.9% and 48.1%, namely. The current study found that compared with children who never participate in sports, those children who participated sports in 1-3 times a month, 1-2 times a week, and 3 times a week and above were more likely to enjoy better well-being. Compared with children who never participate in sports, those children who in every grade participated sports in 1-3 times a month, 1-2 times a week, and 3 times a week and above were more likely to achieve better well-being. Conclusion: Our current study offered the positive effect of sports participation on children and adolescents’ subjective well-being. For schools and governments, further studies are needed to focus on sports participation and positive feedback on adolescents’ mental health, and the three parties’ endeavors should be intervened.